Assessing impacts of CAP reform in France and Germany - Bernd Kup̈ker; Silke Huẗtel; Werner Kleinhanss; Frank Offermann (Agrarwirtschaft: Zeitschrift für Betriebswirtschaft, Marktforschung und Agrarpolitik, 2006)
The 2003 CAP Reform left EU member states much room for national implementation. The farm group model EU-FARMIS is applied to quantify the effects of the reform and the impacts of the options for national implementation. The analysis is done for France and Germany because their implementation schemes adequately reflect the broad range of options. It is found that cereal and fodder maize production is reduced both in France and Germany. In contrast, the acreage of other arable fodder crops, of set-aside and of non-food crops is expanded. While bull fattening is substantially reduced in both countries, suckler cow production is extended in France due to partial decoupling, but reduced in Germany due to full decoupling. Sectoral income effects measured in Farm Net Value Added are similar. The regional implementation of decoupling in Germany induces a significant redistribution of direct payments and therefore causes differences in income effects depending on farm type, location and size.
Keywords: 330; EU-Agrarpolitik; Agrarreform; Wirkungsanalyse; Agrarboden; Agrarproduktion; Agrareinkommen; Frankreich; Deutschland